Current Diagnostic Approach of Inflammmatory Bowel Disease - Anggilia Stephanie; Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2014)
Inflammatory bowel disease (IBD) has begun to emerge in Indonesia. The disease is further classifiedinto two types, ulcerative colitis (UC) and Crohn's disease (CD). Diagnosis of IBD is initiated from symptomfindings such as diarrhea, abdominal pain, bleeding diarrhea, and weight loss, and supported by physicalexamination and additional tests. The options for additional examinations of IBD are mainly endoscopy (esophagogastroduodenoscopy, colonoscopy, and also intestinal endoscopy), imaging techniques, and laboratory examinations either from blood or feces. The application of these modalities should be prompted by sufficientclinical suspicion to promote their efficiency as well as prevent underdiagnosis or overdiagnosis. In primaryhealth care settings, patients with IBD are expected to be recognized for therapy or to use appropriate referralsystem to warrant a proper treatment.Keywords: inflammatory bowel disease, diagnosis terkini, kolitis ulseratif, penyakit Crohn ABSTRAKInflammatory bowel disease (IBD) mulai banyak ditemukan di Indonesia. Penyakit ini terbagi atas dua jenisyaitu kolitis ulseratif (KU) dan penyakit Crohn (PC). Diagnosis IBD dimulai dari gejala yang ditemukan sepertidiare, nyeri perut, buang air besar berdarah dan penurunan berat badan, serta didukung oleh pemeriksaan fisikdan pemeriksaan penunjang. Pilihan pemeriksaan penunjang untuk IBD secara garis besar adalah endoskopi(esofagogastroduodenoskopi, kolonoskopi maupun endoskopi usus halus), pencitraan, dan pemeriksaanlaboratorium, baik dari darah atau feses. Penggunaan berbagai modalitas ini harus didahului adanya kecurigaanyang cukup secara klinis agar tepat guna, mencegah under- atau overdiagnosed. Pada tingkat layanan primer,pasien IBD juga diharapkan dapat ditemukan untuk diterapi atau menggunakan sistem rujukan yang tepat agar ditatalaksana dengan baik.Kata kunci: inflammatory bowel disease, diagnosis terkini, kolitis ulseratif, penyakit Crohn